Microbiological safety criteria for products from unconventional raw materials: raw bear fat - Elena A. Vechtomova; Irina V. Dolgolyuk; Maria M. Orlova; Alexandra V. Zaushintsena (Foods and Raw Materials, 2023)
Fat of game animals is a prospective raw material for bioactive additives. Before such a product enters the market, food science has to make sure it is safe for consumption. This research featured subcutaneous adipose tissue of brown bears tested with standard methods for microbiological safety indicators. The microbial properties were studied on liquid and solid nutrient media. Staphylococcus was profiled using a VITEK 2 Compact biochemical automatic analyzer and Gram-positive cards (Bio-Mérieux, France). The analysis followed the Technical Regulations of the Customs Union TR TS 021/2011 On Food Safety (December 09, 2011). The microbial count for mesophilic aerobic and facultative anaerobic microorganisms was 1.5×103 CFU/g. The fat samples revealed no molds, yeasts, or Escherichia coli bacteria. Liquid and solid nutrient media made it possible to describe the qualitative profile and cultural properties of the bear fat microflora against pork fat, which served as control. The automatic system identified Gram-positive, coagulase-negative, and oxidase-positive Staphylococcus lentus and Staphylococcus sciuri. In line with the modern classification, they belong to the new genus of Mammaliicoccus, namely Mammaliicoccus sciuri. Subcutaneous adipose tissue of brown bears needs to undergo a microbiological safety test before consumption. Bear fat requires additional research in order to become a safe raw material for food products and bioactive additives.